Respostas

2014-04-09T23:49:02-03:00
Primeiramente

3X-2A=B
3X=B+2A
X= \frac{B+2A}{3}

Fazendo
B+2A
\left[\begin{array}{cc}5&-1\\3&4\end{array}\right]+2\left[\begin{array}{cc}-2&2\\-3&3\end{array}\right]\\\\\\ \left[\begin{array}{cc}5&-1\\3&4\end{array}\right]+\left[\begin{array}{cc}-4&4\\-6&6\end{array}\right]\\\\\ \left[\begin{array}{cc}1&3\\-3&10\end{array}\right]\\\\

X=\frac{\left[\begin{array}{cc}1&3\\-3&10\end{array}\right]\\\\}{3}\\\\ x=\left[\begin{array}{cc}\frac{1}{3}&1\\-1&\frac{10}{3}\end{array}\right]\\\\

Letra B